Everything goes - By sea - Biggs, Brian (Balzer + Bray / HarperCollins, 2013)
"A young boy learns about all kids of water vehicles as he and his parents take off on a seaborne journey"--
Keywords: Boats and boating / Fiction; Ships / Fiction; Vehicles / Fiction; Boats and boating / Juvenile fiction; Ships / Juvenile fiction; Vehicles / Juvenile fiction